(untitled) (SAARC Journal of Agriculture, 2014)
A field experiment was conducted during 2007-2009 in the instructional farm of Uttar Banga Krishi Viswavidyalaya, West Bengal, India to find out the effect of integrated nutrient management on oil and protein yield of Rapeseed (Brassica campestris var. Yellow sarson). The experiment was laid out in randomized block design with 12 treatments viz., 100% Recommended Dose Fertilizer (RDF) 60:30:30 Kg ha-1 of N: P: K (T1), 100% RDF + Borax @ 10.0 Kg ha-1 (T2), FYM @ 10.0 t ha-1 (T3), Vermicompost @ 5.0 t ha-1 (T4), Neemcake @ 5.0 t ha-1 (T5), Poultry manure @ 5.0 t ha-1 (T6), T1+ FYM @ 5.0 t ha-1 (T7), T1+ Vermicompost (VC) @ 2.5 t ha-1 (T8), T1+ Neemcake (NC) @ 2.5 t ha-1 (T9), T1+ Poultry Manure (PM) @ 2.5 t ha-1 (T10), 50% RDF+ FYM @ 2.5 t ha-1 + VC @1.25 t ha-1 + NC @ 1.25 t ha-1 + PM @ 1.25 t ha-1 (T11) and Control (T12) and replicated thrice. Average results of oil and protein content and their respective yields was maximum (44.99 & 29.84% and 606.33 & 402.11 kg ha-1 respectively) in the crop fertilized with 50% RDF + FYM @ 2.5 t ha-1 + VC @1.25 t ha-1 + NC @ 1.25 t ha-1 + PM @ 1.25 t ha-1 (T11) followed by T9 i.e. application of T1+ Neemcake @ 2.5 t ha-1 (44.81 & 29.22% and 600.67 & 391.50 kg ha-1 respectively) and T8 i.e. application of T1+ Vermicompost @ 2.5 t ha-1 (44.24 & 29.01 and 585.33 & 383.67 kg ha-1 respectively). Based on pooled data T11 treatment recorded maximum seed yield of 1347.68 kg ha-1 which was statistically at par with T9 (1340.47 kg ha-1), However, treatment T1 (100 % RDF) showed highest BCR (3.85) due to low cost of cultivation. DOI: http://dx.doi.org/10.3329/sja.v10i2.18322 SAARC J. Agri., 10(2): 41-49 (2012)